THE EFFECT OF NON PERFORMING LOANS, OPERATING EXPENSE TO OPERATING INCOME, AND LOAN TO DEPOSIT RATIO ON STOCK RETURN AT CONVENTIONAL BANKS - Iskandar, Yusuf (Jurnal Entrepreneur dan Entrepreneurship, 2017)
This research is conducted to determine the effect of NPL, BOPO, and LDR on Stock Return of private banks and government banks as conventional banks in Indonesia. This research uses multiple linear regression analysis with three predictors. The results show that NPL and LDR have no significant effect on Stock Return, while BOPO has significant effect on Stock Return.